Implementasi Sistem Informasi Manajemen Laporan Pengaduan Masyarakat Pengguna Air Bersih - Risma Petrus; Nur Jamila; Armin Yikwa (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2023)
The development of a complaint report management system in Manokwari was carried out in a structured and directed manner to make it easier for employees to manage public complaint data. The methods and approaches used in the research are data collection methods including literature studies and interviews as well as a structural approach that uses several tools and techniques to build public complaint applications. By implementing the development of a web-based complaint report management system in Manokwari using the programming languages HTML, CSS, PHP, XAMPP, Boostrap and SublamText 3, it is hoped that it will make it easier for employees to process public complaint data.